Effects of varenicline on the serum levels of olanzapine in male patients with Schizophrenia: a randomized controlled trial - Deng, Mengling; Yang, Zhi; Ni, Yanfei; Zhu, Lingli; Xu, Jiating; Zheng, Lifeng; Zhou, Bo (Frontiers in Psychiatry, 2023)
Background Smoking in patients with Schizophrenia is more common than in the general population. Varenicline, a partial agonist at α4β2 nicotinic acetylcholine receptors, is an effective smoking cessation pharmacotherapy in patients with Schizophrenia. However, its effects on the serum levels of antipsychotics in Schizophrenia are understudied. This study investigated the impact of smoking cessation with varenicline on the serum concentration of olanzapine in patients with Schizophrenia. Methods Adult smokers with Schizophrenia were enrolled in a 12-week course of varenicline and placebo for smoking cessation. The serum concentration of olanzapine was measured at baseline and weeks 1, 2, 4, 8, and 12. Data were analyzed with the generalized additive mixed model. Results During the 12-week study, the results indicated that olanzapine concentrations increased nonlinearly in the varenicline and placebo groups. Threshold effect analysis suggested that the olanzapine concentrations increased over time until the turning point (week 4). However, there was no significant difference between the two treatment groups. Conclusion Varenicline showed safety and efficacy in smoking cessation in people with Schizophrenia.